819. Antibiotic Resistance in Pathogens Causing Hospital Acquired Infections in Brazil: A Multicenter Study. (4th December 2021) - Starling, Carlos; Couto, Bráulio R G M; Silva, Estevão Urbano; Andrade, Virginia; Leite, Edna M M; Gonçalves, Simony; Melo, Mariana; Bandeira, Raquel; Carvalho, Priscila; Pereira, Hoberdan; Fernandes, Rafael; Mata, Camila; et al.
Abstract: Background: In the present study we determined the prevalence of antibiotic resistance in the most common organisms causing healthcare-associated infections in tertiary-care hospitals in Belo Horizonte, a 3, 000, 000 inhabitants city from Brazil. Methods: Microbiology data of hospital acquired infections (HAI) defined by the National Healthcare Safety Network (NHSN)/CDC protocols of seven general hospitals were analyzed: three public institutions, two philanthropic, and two private hospitals. Samples from different topographies were plate in an ideal culture medium and after growth, the microorganisms were identified by standard biochemical and microbiological methods, using the VITEK 2 compact system (Biomerieux), which allows the simultaneous identification of Gram-positive and Gram bacteria -negative and combine the identification and TSA results in a single report. Six hospitals used automated methods and one institution used manual method for antimicrobial susceptibility testing. Results: Samples of seven Gram-negative and two Gram-positive bacteria collected between Dec/2019-Nov/2020 from HAI isolates were analyzed: 565 Klebsiella, 293 Escherichia coli, 153 Proteus, 403 Pseudomonas, 275 Acinetobacter, 174 Serratia, 153, 361 Staphylococcus aureus, and 176 Enterococcus . Antibiotic resistance profile of each strain is summarized in Figures 1, 2, and 3. Resistance profile: Klebsiella, E. coli, Proteus. ATB profile: Pseudomonas, Acinetobacter, Serratia. ATB profile: Enterobacter, S. aureus, Enterococcus . Conclusion: Benchmarks for antibiotic resistance in the most common organisms causing healthcare-associated infections were defined, and can be used as indicators for healthcare assessment, specially in developing countries institutions. Disclosures: All Authors : No reported disclosures